MENINGKATKAN HASIL BELAJAR IPA PADA MATERI BENDA DAN SIFAT-SIFATNYA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DI KELAS III SEKOLAH DASAR - Owen Rano Halasson Silitonga; Marlin Simangungsong (Jurnal Mutiara Pendidikan Indonesia, 2018)
This study aims to improve students' mathematics learning outcomes multiplication material by using a contextual teaching and learning model class III SD Negeri 026602 Tanah Seribu Binjai Selatan. Based on the results of the study showed that there was an increase in Student Learning Outcomes Using the Contextuaal Teaching and Learning Model in mathematics multiplication material in class IIIA of SD Negeri 026602 Tanah Seribu Binjai T.A 2018/2019. This is evident from the learning outcomes of students in cycle I and cycle II. Completeness of student learning outcomes in pre-cycle there are 10 students whose learning outcomes are complete (47%) with an average value of 53.91. Student learning outcomes in the first cycle, there are 15 students who graduated with a mastery level of 52.17% with an average value of 73. Then the learning outcomes of students in the second cycle there were 20 students with a mastery level of 86.96% with an average grade 84.34. And the results of the implementation of the observation of the first cycle teacher with a percentage of 73.86% while the observation of the first cycle students the percentage of 70.45 with enough categories. And the learning outcomes of the observation cycle II teacher with a percentage of 86.36% while the learning outcomes of the observation cycle II students with a percentage of 85.22%.